Enzyme protection systems of erythrocytes in conditions of ascorbate recirculation and oxidative loading - O. I. Dotsenko; G. V. Taradina; M. V. Voronych (Regulatory Mechanisms in Biosystems, 2018)
Vitamin C was shown to partially protect red blood cells from oxidative changes during storage by noticeable reduction of mechanical fragility and hemolysis. In order to maintain the content of ascorbate in the reconstituted form in plasma, the latter is involved in a number of oxidative-reducing processes within red blood cells. This work is a continuation of studies of the effects of ascorbate on the metabolic processes that maintain the viability of red blood cells. Human red blood cells were incubated for five hours at 25 ºC in the oxidizing media system 1 1.0 · 10–4 M ascorbic acid (AscH), 5 · 10–6 M Cu2+, Na-phosphate buffer (0.015 M, pH 7.4), 0.15 M NaCl, and system 2, that contained o-phenanthroline at a concentration of 1.0 · 10–4 M in addition to the components of system 1 medium. For these cells, the changes in the content of reduced glutathione, glutathione enzyme activity, and the state of the membrane electron transport NADH: ferricyanide reductase were determined in time. The obtained data indicate that red blood cells undergo significant oxidative stress under the influence of the oxidative medium. During the first incubation period of erythrocytes in the AscH-Cu2+ environment, the activity of glutathione peroxidase and glutathione-S-transferase reached the maximum values, indicating the presence of H2O2 in the cell and the activation of lipid peroxidation processes. Glutathione-S-transferase activity remained above the control level throughout the entire study period. The activity of glutathione reductase and glucose-6-phosphate dehydrogenase was reduced. The oxidative loading of erythrocytes in the presence of o-phenanthroline was lower, the development of oxidative stress occurred in 90 minutes, but the binding of the o-phenanthroline complexes of Cu2+ to the membrane modified the SH-group of membrane proteins and this reduced the transport capabilities of the dehydroascorbate transporters and the electron transmembrane system, the consequence of which may be the accumulation of oxidized forms of ascorbate outside. We detected the participation of CO-signaling mechanism in hemoglobin deglutathionylation and increase in the content of glutathione. In this work we discuss the role of metabolic reprogramming in red blood cells through thiol-disulfide exchange as a mechanism that can be involved into adaptive responses aimed at counteracting stress in mammalian tissues.